Flammability and soil burial performance of sugar palm (Arenga pinnata (wurmb) merr) fiber reinforced epoxy composites - Jamal, Tarique; Salit, Mohd Sapuan (Universiti Putra Malaysia, 2023)
This study investigates the effects of soil burial and flammability on sugar palm fibre (SPF) (Arenga pinnata (wurmb) merr)-reinforced epoxy composites. In order to determine the flammability and biodegradability properties, experiments are conducted in accordance with ASTM standards. The hand lay-up method was used to fabricate composite samples with two different weight ratios between epoxy and SPF, which were 70:30 and 50:50. Biodegradability and flammability properties were investigated using horizontal burning tests, limiting oxygen index (LOI), cone calorimetry, and soil burial. It was found that the Epoxy/SPF-50 was the composite that exhibited the fastest degradability at 0.81%/week. The result of the horizontal burning test showed that the addition of SPF reduced the burning rate but slightly increased it at 50 wt% because the ratio between epoxy and SPF exceeds the optimum fibre loading. The Epoxy/SPF-50 exhibited a better LOI value at 23.3 than pure epoxy (control), which was 19.8. From the cone calorimetry test, it was observed that the time to ignition (TTI) and total heat release (THR) values were decreased when the amount of SPF increased. Char production increases the flame-retardant protection of SPF-reinforced epoxy composites. To the best of the authors’ knowledge, no published study has been conducted on the flammability and biodegradability characteristics of SPF-reinforced epoxy composites.